Proposed Algorithm of Tone Reservation PAPR Reduction in OFDM System - Chaiel, Hussain K.; Nasir, Hassan Abbu (Basrah Journal for Engineering Sciences, 2010)
Orthogonal frequency division multiplexing (OFDM) has become a popular modulation method in high-speed wireless communication systems due to its high data rate transmission capability and robustness against multipath fading effects. One of the major drawbacks of OFDM at the transmitter side is the high peak-to-avenge power ratio (PAPR) of the OFJ)M signal. In this paper, an algorithm is proposed to reduce the peak-to-average power ratio of OFDM signal with a large number of sub-carriers. This algorithm is based on the tone reservation method. The computer simulation tests show that the suggested algorithm reduces the PAPR to a factor of S.2S dB and needs less number of iterations as compared with the traditional tone reservation algorithm.